HASIL BELAJAR KOGNITIF FISIKA SISWA MELALUI STRATEGI TANDUR DI KELAS X IIS 4 LINTAS MINAT SMAN 12 PEKANBARU - Gina Syahvina Syahvina; M.Rahmad '; M. Sahal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study aimed to describe the students' cognitive learning outcomes and feasibility TANDUR strategies on learning materials and Heat Temperatures in Class X IIS 4 SMAN 12 Pekanbaru. The subjects were students of class X IIS 4 of 32 people consisting of 15 male students and 17 female students. Data collection instruments in this research is to test the cognitive learning through the pretest and posttest consisting of 16 multiple choice items and pieces feasibility TANDUR strategy. The research analyzed descriptively to see an overview of cognitive learning outcomes using the criteria of absorption, the effectiveness of learning, mastery learning and feasibility picture TANDUR strategy. Results of data analysis obtained an average absorption capacity for pretest 34.77% (unfavorable category) and posttest 80.07% (both categories), mastery learning students to pretest 0% (Not Completed) and posttest 87.5% (Completed ), mastery learning materials for pretest 12.5% ​​(Not Completed) and posttest 81.25% (Not Completed). Thus the implementation of effective strategies in class X TANDUR IIS 4 SMAN 12 Pekanbaru. KeyWords:learning outcomes students, TANDUR strategy, heat and temperature